Iron maltol-quercetin eutectic crystal and preparation method thereof

By developing iron maltol-quercetin co-crystals, the problems of gastrointestinal side effects and high solubility in clinical applications of existing iron maltol maltol preparations have been solved, and the stability and efficacy of drug release speed have been improved.

CN119638661AActive Publication Date: 2025-03-18JINLING PHARMA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411802977.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-18
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing maltol iron preparations have gastrointestinal side effects and are highly soluble in clinical applications, resulting in unstable drug release rate and affecting the efficacy.

Method used

A maltol iron-quercetin eutectic was developed, prepared by suspension stirring, quercetin was introduced as a eutectic ligand, reducing the gastrointestinal side effects of maltol iron and optimizing the physical and chemical properties of the drug through physical means.

Benefits of technology

The maltol iron-quercetin eutectic is stable under accelerated conditions, extending the shelf life of the preparation, reducing the risk of drug efficacy and quality problems, ensuring that the drug is released in the body is more stable and long-lasting, reducing adverse gastrointestinal inflammatory reactions, and achieving the best clinical efficacy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638661A_ABST
    Figure CN119638661A_ABST
Patent Text Reader

Abstract

The invention discloses an iron maltol-quercetin eutectic which has characteristic diffraction peaks in an X-ray powder diffraction pattern measured by using Cu-K alpha radiation when diffraction angles 2 theta are about 8.6 + / -0.2 degrees, 11.1 + / -0.2 degrees, 12.1 + / -0.2 degrees, 15.0 + / -0.2 degrees, 20.1 + / -0.2 degrees, 22.9 + / -0.2 degrees, 23.4 + / -0.2 degrees, 25.0 + / -0.2 degrees and 26.4 + / -0.2 degrees. The iron maltol-quercetin eutectic crystal is good in stability, and does not generate crystal transformation in at least 60 days under an accelerated condition (40 DEG C, 75% RH). By introducing the eutectic ligand quercetin, the iron maltol-quercetin eutectic crystal has relatively low solubility and slow dissolution rate, can ensure that the in-vivo release rate of a drug is more stable and lasting, avoids a drug concentration peak value in a short time, and can reduce the side effect of adverse reaction of gastrointestinal inflammation caused by iron maltol.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of medical technology and relates to a drug cocrystal, and specifically relates to a maltol iron-quercetin cocrystal and a preparation method thereof. Background Art

[0002] Ferric maltol is a new type of non-salt complex formed by iron and maltol with stable chemical properties. It is a reddish brown crystalline solid with the following chemical structure:

[0003]

[0004] Maltol iron can provide iron, supplement the nutrients needed by the body, and prevent or treat iron deficiency anemia. Maltol iron has a unique absorption mechanism and has obvious advantages over similar iron supplements. Maltol iron capsules, developed by Shield Therapeutics in the UK, were approved by the European Medicines Agency (EMA) and the US Food and Drug Administration (FDA) in 2016 and 2019 for the treatment of iron deficiency in adults (with or without anemia symptoms). The trade names are Feraccru (EU market) and Accrufer (US market). A series of clinical trials have confirmed that maltol iron capsules are an oral drug for the treatment of iron deficiency in adults with a low incidence of adverse reactions, high bioavailability, low iron overload, and good tolerance. For patients who are intolerant to existing oral iron preparations or have poor treatment effects, maltol iron capsules are an ideal alternative. It is reported that the main adverse reactions of ferric maltol include gastrointestinal inflammation, gastrointestinal flatulence, constipation, diarrhea, etc. (Khoury A, Pagan KA, Farland MZ. Ferric maltol: A new oral iron formulation for the treatment of iron deficiency in adults. Ann Pharmacother. 2021, 55(2): 222-229).

[0005] Quercetin is a natural product with good biological activity. It is a dietary polyphenol that has the ability to scavenge free radicals and can also induce the activation of antioxidant and detoxification enzymes, thereby protecting cells from oxidative damage by carcinogenic compounds. Quercetin mainly exists in vegetables, fruits, tea, and wine in the form of glycosides. It has a wide range of sources and is safe and easy to obtain. Quercetin has been widely recognized in the treatment of diabetes, hypertension, anti-aging, and analgesic effects. It is reported that quercetin has good safety and multifaceted anti-inflammatory pharmacological activity, can relieve colitis symptoms, maintain colon length and intestinal barrier integrity (Wang X, Xie X, Li Y, et al., Quercetin ameliorates ulcerative colitis by activating aryl hydrocarbon receptor to improve intestinal barrier integrity. Phytother. Res. 2023, 38 (1): 253-264).

[0006] A drug cocrystal refers to a crystal formed by the active drug molecules and cocrystal ligands in the same crystal lattice in a fixed stoichiometric ratio through non-ionic bonds and non-covalent bonds. It does not change the chemical structure of the original drug, but optimizes the physicochemical properties of the drug by physical means, such as improving solubility, enhancing stability and improving bioavailability.

[0007] There is no report on maltol-iron eutectic so far, so it is of great significance to develop a maltol-iron eutectic product with excellent stability. Summary of the invention

[0008] The purpose of the present invention is to provide a maltol iron-quercetin cocrystal and a preparation method thereof. The maltol iron-quercetin cocrystal is composed of maltol iron and a medicinal small molecule excipient quercetin. The introduction of the ligand quercetin can reduce the gastrointestinal side effects of maltol iron to achieve the best clinical efficacy; the maltol iron-quercetin cocrystal can be prepared into a variety of dosage forms such as tablets, capsules, transdermal patches, inhalants, etc., which are suitable for different administration methods.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] A maltol iron-quercetin eutectic is a eutectic formed by using maltol iron as a pharmaceutical active ingredient and quercetin as a eutectic ligand through a suspension stirring method.

[0011] In the X-ray powder diffraction pattern measured using Cu-Kα radiation, the maltol iron-quercetin cocrystal has characteristic diffraction peaks at diffraction angles 2θ of approximately 8.6±0.2°, 11.1±0.2°, 12.1±0.2°, 15.0±0.2°, 20.1±0.2°, 22.9±0.2°, 23.4±0.2°, 25.0±0.2°, and 26.4±0.2°, and the 2θ angle of the characteristic peak with a relative intensity of 100% is 20.1±0.2°.

[0012] Preferably, the maltol iron-quercetin cocrystal has Figure 1 or Figure 5 or Figure 6 The X-ray powder diffraction pattern is shown.

[0013] The infrared absorption spectrum of the maltol iron-quercetin eutectic and potassium bromide (KBr) mixed tablets was measured at 3411.84, 3266.53, 1625.95, 1602.16, 1570.45, 1528.86, 1504.59, 1470.70, 1437.68, 1420.00, 1375.07, 1326 .27, 1274.71, 1200.79, 1167.82, 1099.34, 1042.82, 1019.90, 998.39, 928.84 ,891.12,850.99,786.29,726.56,656.94,621.25,542.83,511.13,417.27cm -1 There are characteristic peaks nearby.

[0014] In the differential scanning calorimetry (DSC) spectrum, the maltol iron-quercetin cocrystal has a single endothermic melting peak at 263.56°C.

[0015] Another object of the present invention is to provide a method for preparing the ferrous maltol-quercetin cocrystal, which adopts a suspension stirring method and comprises the following steps: adding ferrous maltol and quercetin to an organic solvent to form a suspension, stirring the reaction, filtering, and drying to obtain the ferrous maltol-quercetin cocrystal.

[0016] The ratio of the amount of maltol iron to quercetin is 1:0.5 to 1:3, preferably 1:1 to 1:2, and more preferably 1:1.

[0017] The organic solvent is anhydrous ethanol, methanol, acetonitrile, acetone, ethyl acetate or a mixed solvent of at least two of the above organic solvents. In view of the reaction rate and the yield of the eutectic, anhydrous ethanol or methanol is preferred.

[0018] The dosage ratio of the maltol iron to the organic solvent is 2:1-500:1 mg / mL, preferably 50 mg:1-200:1 mg / mL.

[0019] The reaction temperature is 15-50°C, preferably 25-35°C, and most preferably room temperature (25°C).

[0020] The reaction time is 2 to 7 days, preferably 5 to 6 days.

[0021] The rotation speed of the stirring reaction is 50 to 1000 rpm, preferably 200 to 400 rpm.

[0022] Another object of the present invention is to provide a pharmaceutical composition comprising the ferrous maltol-quercetin cocrystal and a pharmaceutically acceptable carrier.

[0023] The dosage form of the pharmaceutical composition is tablets, capsules, transdermal patches, inhalants and other dosage forms.

[0024] Beneficial effects of the present invention:

[0025] (1) The PXRD, DSC and IR spectra of the ferrous maltol-quercetin eutectic of the present invention are different from those of ferrous maltol crystals, quercetin crystals and the ferrous maltol-quercetin physical mixture, and the eutectic is a new solid state completely different from the existing ferrous maltol and quercetin.

[0026] (2) The maltol iron-quercetin cocrystal of the present invention does not undergo crystal transformation under accelerated conditions (40°C, 75% RH) for at least 60 days, has good stability, can extend the shelf life of the cocrystal preparation, reduce the decline in efficacy and quality problems caused by crystal transformation, and reduce the risks of production and quality control.

[0027] (3) Compared with ferric maltol, the ferric maltol-quercetin eutectic has relatively low solubility and slow dissolution rate by introducing the eutectic ligand quercetin, which can ensure that the drug is released in the body at a more stable and lasting rate, avoid the peak drug concentration in a short period of time, and provide a new solution for the design of sustained-release and long-acting drug release system. It can also reduce the side effects of gastrointestinal inflammatory adverse reactions caused by ferric maltol, exert the effect of synergistic treatment, and achieve the best clinical efficacy.

[0028] (4) Compared with amorphous solid dispersion technology, which usually requires a polymer carrier several times the amount of the drug to fully disperse the drug, the maltol iron-quercetin cocrystal of the present invention has a high drug loading and better stability; compared with nanotechnology, the maltol iron-quercetin cocrystal of the present invention is easier to industrialize and its quality is easier to control.

[0029] (5) The preparation method of the maltol iron-quercetin eutectic of the present invention is simple, low-cost, easy to control, and conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the PXRD pattern of the maltol iron-quercetin cocrystal prepared in Example 1.

[0031] Figure 2 This is a PXRD comparison diagram of the ferrous maltol-quercetin eutectic prepared in Example 1, ferrous maltol, and quercetin.

[0032] Figure 3 It is a DSC comparison chart of the ferrous maltol-quercetin cocrystal, ferrous maltol and quercetin prepared in Example 1.

[0033] Figure 4 This is a comparison chart of infrared spectra of the ferrous maltol-quercetin eutectic, the ferrous maltol-quercetin physical mixture, quercetin and ferrous maltol prepared in Example 1.

[0034] Figure 5 This is the PXRD pattern of the maltol iron-quercetin cocrystal prepared in Example 2.

[0035] Figure 6 This is the PXRD pattern of the maltol iron-quercetin cocrystal prepared in Example 3.

[0036] Figure 7 This is a PXRD comparison chart of the maltol iron-quercetin cocrystal in Example 1 placed under accelerated conditions (40° C., 75% RH) for 60 days and 0 day.

[0037] Figure 8 This is the PXRD pattern of the product prepared by slurrying maltol iron and L-histidine in ethanol, acetonitrile, ethyl acetate and acetone in Comparative Example 1.

[0038] Fig. 9 This is the PXRD pattern of the product prepared by slurrying maltol iron and nicotinamide in ethanol, acetonitrile, ethyl acetate and acetone in Comparative Example 2. DETAILED DESCRIPTION

[0039] The maltol iron used in preparing the maltol iron-quercetin eutectic is maltol iron crystal form II; the maltol iron (crystal) used for comparison with the maltol iron-quercetin eutectic is maltol iron crystal form II.

[0040] Example 1

[0041] Preparation of maltol iron-quercetin cocrystal

[0042] According to the feeding molar ratio of maltol iron to quercetin of 1:1, 100 mg of maltol iron and 70.1 mg of quercetin were weighed, 0.5 mL of anhydrous ethanol was added, and magnetic stirring (speed 400 rpm) was carried out at room temperature (25°C) for 6 days. The filter cake was vacuum dried at 40°C for 24 hours to obtain maltol iron-quercetin eutectic as a dark red solid.

[0043] The maltol iron-quercetin cocrystal was characterized by X-ray powder diffraction (PXRD) instrument, using Cu-Kα radiation, and the PXRD pattern was as follows Figure 1 shown.

[0044] Comparing the PXRD patterns of maltol iron-quercetin eutectic with maltol iron crystals and quercetin crystals, such as Figure 2 As shown, it can be seen that the PXRD pattern of ferrous maltol-quercetin cocrystal is significantly different from that of ferrous maltol and quercetin. Further comparison of the characteristic peaks of the three, as shown in Table 1, shows that the cocrystal has characteristic diffraction peaks that are significantly different from ferrous maltol and quercetin at diffraction angles 2θ of approximately 8.64°, 11.14°, 12.14°, 14.96°, 20.13°, 22.88°, 23.40°, 24.99°, and 26.43°.

[0045] Table 1. Comparison of PXRD characteristic diffraction peak positions of ferrous maltol-quercetin cocrystal and ferrous maltol and quercetin

[0046]

[0047]

[0048] The thermal properties of ferric maltol, quercetin and the ferric maltol-quercetin eutectic prepared in this example were analyzed by differential scanning calorimetry (DSC). The method is as follows: take about 3 mg of sample, set the flow rate of nitrogen purge gas in the sample chamber to 100 mL / min, balance at 25°C, and heat to 400°C at a heating rate of 10°C / min. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that the thermal behaviors of ferric maltol-quercetin eutectic, ferric maltol and quercetin are significantly different. The melting point of ferric maltol is 288.87°C, the melting point of quercetin is 318.05°C, and the melting point of ferric maltol-quercetin eutectic is 263.56°C.

[0049] Comparison of infrared spectra of ferrous maltol-quercetin cocrystal: ferrous maltol, quercetin and the ferrous maltol-quercetin cocrystal prepared in this example were characterized by Fourier transform infrared spectroscopy, and the spectrum acquisition range was 4000-400 cm -1Before recording the spectrum of each sample, the air was used as a blank for measurement. Comparison of infrared detection spectra of ferric maltol, quercetin, ferric maltol-quercetin physical mixture (the molar ratio of ferric maltol to quercetin is 1:1) and ferric maltol-quercetin eutectic prepared in this example Figure 4 As shown. Figure 4 It can be seen that the maltol iron-quercetin eutectic is at 3411.84, 3266.53, 1625.95, 1602.16, 1570.45, 1528.86, 1504.59, 1470.70, 1437.68, 1420.00, 1375.07, 1326.27, 1274.71, 1200.79, 1167.82, 1099.34, 1042.82, 1019.90, 998.39, 928.84, 891.12, 850.99, 786.29, 726.56, 656.94, 621.25, 542.83, 511.13, 417.27cm -1 There are characteristic peaks nearby, which are significantly different from ferrous maltol and quercetin, and the physical mixture of ferrous maltol and quercetin.

[0050] Example 2

[0051] Preparation of maltol iron-quercetin cocrystal

[0052] According to the molar ratio of maltol iron to quercetin of 1:2, 100 mg of maltol iron and 140.2 mg of quercetin were weighed, 0.5 mL of anhydrous ethanol was added, and magnetic stirring (speed 400 rpm) was carried out at room temperature (25°C) for 6 days, and the filter cake was vacuum dried at 40°C for 24 hours to obtain a dark red solid, which was characterized by PXRD. Using Cu-Kα radiation, the PXRD spectrum is as follows: Figure 5 As shown. Figure 5 It can be seen that the characteristic diffraction peaks of this product are basically consistent with those of the product in Example 1, and maltol iron-quercetin cocrystals are also obtained.

[0053] Example 3

[0054] Preparation of maltol iron-quercetin cocrystal

[0055] According to the molar ratio of maltol iron to quercetin of 1:1, 100 mg of maltol iron and 70.1 mg of quercetin were weighed, 0.5 mL of anhydrous ethanol was added, and magnetic stirring (speed 200 rpm) was carried out at room temperature (25°C) for 6 days, and the filter cake was vacuum dried at 40°C for 24 hours to obtain a dark red solid, which was characterized by PXRD. Using Cu-Kα radiation, the PXRD spectrum is as follows: Figure 6 As shown. Figure 6It can be seen that the characteristic diffraction peaks of this product are basically consistent with those of the product in Example 1, and maltol iron-quercetin cocrystals are also obtained.

[0056] Example 4

[0057] Study on the stability of maltol iron-quercetin eutectic

[0058] The maltol iron-quercetin eutectic prepared in Example 1 was placed in a constant temperature and humidity chamber under accelerated conditions (40°C, 75% RH), and samples were taken on the 60th day and characterized using an X-ray powder diffractometer (PXRD). The results are shown in FIG. Figure 7 As shown. Figure 7 It can be seen that the maltol iron-quercetin cocrystal does not undergo crystal transformation under accelerated conditions for at least 60 days.

[0059] Table 2. Comparison of PXRD characteristic diffraction peak positions of maltol iron-quercetin eutectic at 40℃ and 75%RH for 0 and 60 days

[0060]

[0061] Example 5

[0062] Solubility determination

[0063] Test solution: 5 mL of water was measured and placed in a vial, and an excess of ferric maltol or ferric maltol-quercetin eutectic (Example 1) was added respectively. The vial was sealed, and magnetic stirring was placed at 25° C. to reach equilibrium (24 h), and then filtered through a 0.22 μm microporous membrane to obtain the test solution.

[0064] Reference solution: Take 5.0 mg of maltol iron reference, weigh accurately, place in a 100 mL volumetric flask, add water to dissolve and dilute to the scale, shake well, filter through a 0.22 μm microporous filter membrane, and obtain.

[0065] Determination of maltol iron content: Determine by ultraviolet spectrophotometry at a wavelength of 411nm.

[0066] The results show that at a temperature of 25°C, the solubility of ferric maltol-quercetin cocrystal in water is 7.08 mg / mL, which is lower than the solubility of ferric maltol crystals (9.03 mg / mL). The ferric maltol-quercetin cocrystal with relatively low solubility usually dissolves slowly. From the perspective of formulation, the ferric maltol-quercetin cocrystal of the present invention has some unique advantages, especially in the design and development of sustained-release pharmaceutical preparations, the low-solubility cocrystal can be used to design a long-acting drug release system to ensure that the drug is released in the body at a more stable and lasting rate, avoiding the peak drug concentration in a short period of time.

[0067] Comparative Example 1

[0068] Preparation of maltol iron and L-histidine cocrystal

[0069] According to the molar ratio of maltol iron to L-histidine of 1:1, 100 mg of maltol iron and 35.98 mg of L-histidine were weighed, 0.5 mL of anhydrous ethanol (or acetone, ethyl acetate, acetonitrile) was added, and magnetic stirring (speed 400 rpm) was carried out at room temperature (25°C) for 6 days, and the filter cake was vacuum dried at 40°C for 24 hours to obtain a dark red solid, which was characterized by X-ray powder diffractometer (PXRD). The results are as follows: Figure 8 As shown. Figure 8 It can be seen that the characteristic diffraction peaks of the obtained product are basically consistent with those of ferric maltol and L-histidine, that is, ferric maltol and L-histidine cannot form a eutectic.

[0070] Comparative Example 2

[0071] Preparation of maltol iron and nicotinamide cocrystal

[0072] According to the molar ratio of maltol iron to nicotinamide of 1:1, 100 mg of maltol iron and 28.33 mg of nicotinamide were weighed, 0.5 mL of anhydrous ethanol (or acetone, ethyl acetate, acetonitrile) was added, and magnetic stirring (speed 400 rpm) was carried out at room temperature (25°C) for 6 days, and the filter cake was vacuum dried at 40°C for 24 hours to obtain a dark red solid, which was characterized by X-ray powder diffractometer (PXRD). The results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the characteristic diffraction peaks of the obtained product are basically consistent with those of ferrous maltol and nicotinamide, that is, ferrous maltol and nicotinamide cannot form a eutectic.

Claims

1. A maltol iron-quercetin eutectic, characterized in that: In the X-ray powder diffraction pattern measured using Cu-Kα radiation, it has characteristic diffraction peaks at diffraction angles 2θ of approximately 8.6±0.2°, 11.1±0.2°, 12.1±0.2°, 15.0±0.2°, 20.1±0.2°, 22.9±0.2°, 23.4±0.2°, 25.0±0.2°, and 26.4±0.2°.

2. The maltol iron-quercetin eutectic according to claim 1, characterized in that: The maltol iron-quercetin cocrystal has an X-ray powder diffraction pattern as shown in FIG. 1 , FIG. 5 , or FIG. 6 .

3. The maltol iron-quercetin eutectic according to claim 1, characterized in that: The infrared absorption spectrum of maltol iron-quercetin cocrystal is 3411.84, 3266.53, 1625.95, 1602.16, 1570.45, 1528.86, 1504.59, 1470.70, 1437.68, 1420.00, 1375.07, 1326.27, 1274.71, 1200.79, 1167.82, 1099.34, 1042.82, 1019.90, 998.39, 928.84, 891.12, 850.99, 786.29, 726.56, 656.94, 621.25, 542.83, 511.13, 417.27cm -1 There is a characteristic peak near it; in the differential scanning calorimetry spectrum, the melting point of maltol iron-quercetin cocrystal is 263.56℃.

4. The maltol iron-quercetin eutectic according to claim 1, characterized in that: The eutectic is formed by using maltol iron as the active ingredient and quercetin as the eutectic ligand through a suspension stirring method.

5. A method for preparing the maltol iron-quercetin cocrystal according to claim 1, characterized in that: include: The ferrous maltol and quercetin are added into an organic solvent, stirred for reaction, filtered and dried to obtain the ferrous maltol-quercetin eutectic.

6. The method for preparing the maltol iron-quercetin eutectic according to claim 5, characterized in that: The ratio of the amount of maltol iron to quercetin is 1:0.5 to 1:3, preferably 1:1 to 1:2, and more preferably 1:

1.

7. The method for preparing maltol iron-quercetin cocrystal according to claim 5, characterized in that: The organic solvent is ethanol, methanol, acetonitrile, acetone, ethyl acetate or a mixed solvent of at least two of the above organic solvents.

8. The method for preparing the maltol iron-quercetin cocrystal according to claim 5 or 7, characterized in that: The dosage ratio of the maltol iron to the organic solvent is 2:1-500:1 mg / mL, preferably 50 mg:1-200:1 mg / mL.

9. The method for preparing maltol iron-quercetin cocrystal according to claim 5, characterized in that: The reaction temperature is 15-50°C, preferably 25-35°C; the reaction time is 2-7 days, preferably 5-6 days.

10. A pharmaceutical composition, characterized in that: The pharmaceutical composition comprises the maltol iron-quercetin cocrystal according to claim 1 and a pharmaceutically acceptable carrier.

Citation Information

Patent Citations

  • Crystalline forms of ferric maltol

    CN107001310A

  • Preparation method of maltol iron crystal form II

    CN112574158A

  • Perazopanib-quercetin eutectic crystal as well as preparation method and application thereof

    CN114751893A

  • Novel crystalline forms of iron maltol complex and process for the preparation

    WO2023152710A2